2019
DOI: 10.1515/jbcpp-2019-0244
|View full text |Cite
|
Sign up to set email alerts
|

Ternary solid dispersion to improve solubility and dissolution of meloxicam

Abstract: Background Meloxicam (MLX) is a potent non-steroidal anti-inflammatory drug with poor solubility. Solid dispersion (SD) is an effective formulation strategy to improve the dissolution rate of poorly water-soluble compounds. Hydroxy propyl methyl cellulose (HPMC) as an inert polymer carrier and nicotinic acid (NA) as disturbance can be used as a matrix of SD. The aim of this study was to determine the effect of MLX-HPMC-NA SD on the solubility and dissolution of MLX. Methods SD was prepared by the solvent eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…The results suggested the formation of amorphous solid dispersion. These results were consistent with previous report (Setyawan et al 2019). Moreover, these results suggested that the addition of water insoluble polymer (ethylcellulose) could prevent the recrystallization process (Hameed 2017).…”
Section: Dscsupporting
confidence: 94%
“…The results suggested the formation of amorphous solid dispersion. These results were consistent with previous report (Setyawan et al 2019). Moreover, these results suggested that the addition of water insoluble polymer (ethylcellulose) could prevent the recrystallization process (Hameed 2017).…”
Section: Dscsupporting
confidence: 94%
“…The results of the solubility test on S1, S2 and S3 observed in distilled water were 0.485, 0.2186, 0.1748 respectively as shown in table 3. It was noted that the solubility of the prepared solid dispersion decreased as the ratio of carrier increases [35][36][37].…”
Section: Determination Of Solubility Of Solid Dispersionmentioning
confidence: 99%
“…The carrier used in combination with a ternary agent could be a polymer, surfactant or a polymer with surfactant property [32,33]. Examples of ternary agents comprise surfactant [34], polymer [35], adsorbent [36], pH modulator [37] and hydrotropic agent [38]. Various international publications of the past decade are summarized from the reputed source (Elsevier, Pubmed, NCBI) to emphasize the significance of the key components (ternary agents) particularly, surfactants, polymers, pH modulators, and adsorbents to improve TSD's reliability in addressing the challenges of formulation associated with the drug solubility and dissolution.…”
Section: Introductionmentioning
confidence: 99%